Food Choice and Fitness of Folsomia candida (Collembola, Isotomidae) Fed on Twelve Species of Truffle - Menta, Cristina; Siniscalco, Carmine; Bonati, Beatrice; Remelli, Sara (Frontiers in Environmental Science, 2019)
Fungi are a significant food resource for soil fauna, whose grazing behavior can have a significant impact on their development. This relationship is an important aspect in soil functioning, with soil fungi acting as primary agents in decomposition processes. Being one of the most abundant groups among soil fauna, springtails can play a leading role in this context. Despite several previous studies on their epigeous fungal grazing behavior, data regarding the relationship between springtails and truffles are scarce. This study aimed to investigate food preferences of the springtail Folsomia candida for grazing on 12 different species of truffles, 11 belonging to Tuber genus, and 1 to Balsamia genus. We also evaluated how strongly this diet influences survival and reproduction of F. candida. In the first experiment, F. candida were allowed to choose freely between a cereal mixture (choice test) and 12 different species of truffle. In the second experiment, they were fed on the truffles only (no-choice test) for 28 days. 12 truffle species were analyzed for survival and reproduction of F. candida. F. candida’s feeding preference evolved over 72 hours, beginning with a strong preference for the control and finally a general preference for truffles. Moreover, Collembola that fed on some Tuber species had a lower survival rate and fewer juveniles per adult compared to the control. Compared to other species, Tuber aestivum and Tuber melanosporum, which are well-known for their ability to produce brûlés, had a positive impact on collembolan fitness, whereas their palatability was not particularly prominent. Hence there was a relationship between diet and fitness in F. candida, whilst hardly any relationship was observed between fitness and feeding preference.